2016
DOI: 10.1016/j.cmi.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis, clinical management and infection control of the infections caused by extensively drug-resistant Gram-negative bacilli: a Chinese consensus statement

Abstract: Extensively drug-resistant (XDR) Gram-negative bacilli (GNB) are defined as bacterial isolates susceptible to two or fewer antimicrobial categories. XDR-GNB mainly occur in Enterobacteriaceae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia. The prevalence of XDR-GNB is on the rise in China and in other countries, and it poses a major public health threat as a result of the lack of adequate therapeutic options. A group of Chinese clinical experts, microbiologists and pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 67 publications
3
70
2
Order By: Relevance
“…To circumvent the intrinsic resistance of many mouse strains to A. baumannii infection, artificial models have been used, such as infecting mice intraperitoneally (a clinically irrelevant route of entry) or mixing the inoculum with porcine mucin as a foreign body that inhibits the host's immune system from rapidly clearing the organism (59,60). In addition, mice are often made neutropenic prior to infection even though neutropenia is not a common risk factor for infections caused by A. baumannii, and the vast majority of patients infected with A. baumannii have neither deficiency in leukocyte numbers nor overt defects in leukocyte function (25,(50)(51)(52)(53)(61)(62)(63)(64)(65)(66)(67)(68). Results from such models must be interpreted circumspectly given the unclear applicability to clinical disease.…”
Section: Models Of Infectionmentioning
confidence: 99%
“…To circumvent the intrinsic resistance of many mouse strains to A. baumannii infection, artificial models have been used, such as infecting mice intraperitoneally (a clinically irrelevant route of entry) or mixing the inoculum with porcine mucin as a foreign body that inhibits the host's immune system from rapidly clearing the organism (59,60). In addition, mice are often made neutropenic prior to infection even though neutropenia is not a common risk factor for infections caused by A. baumannii, and the vast majority of patients infected with A. baumannii have neither deficiency in leukocyte numbers nor overt defects in leukocyte function (25,(50)(51)(52)(53)(61)(62)(63)(64)(65)(66)(67)(68). Results from such models must be interpreted circumspectly given the unclear applicability to clinical disease.…”
Section: Models Of Infectionmentioning
confidence: 99%
“…Carbapenems are the most powerful antibiotics for ESBL-producing Enterobacteriaceae. However, for CRGN infections, carbapenems need to be used with other antimicrobial agents for forming antimicrobial combinations and are recommended to be used in a high-dose with minimum inhibitory concentration (MIC) within a certain range [25], which can increase the use of carbapenem and other antibacterial drugs, further aggravate carbapenem resistance and produce new issues of drug resistance. Different from the results of Tan et al [26], which showed no signi cant association between the usage of BL/BLI combinations and the prevalence rates of CRAB, the resistance rate of A. baumannii to carbapenems was positively correlated with cefoperazone-sulbactam usage in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, combination treatments of two or more antibiotics were recommended for the treatment of severe infections with CRAB, aiming to achieve bactericidal effects through synergies at concentrations below the respective MIC of the relevant substances [28]. Among the many combination therapies, cefoperazone/sulbactam-based combination regimen, which is usually combined with tigecycline, minocycline, carbapenems or aminoglycosides, is most commonly used for the treatment of carbapenem-resistant and extensively drug-resistant A. baumannii infections [25]. Therefore, it is understandable that increased consumption of cefoperazone-sulbactam and tetracyclines is associated with carbapenem resistance of A.baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…29; 30; 31; 32 . There are many risk factors for ESBL infection in patients with non-ESBL-EC BSI, so clinicians tend to choose antimicrobial agents covering ESBL-producing bacteria as empirical antibiotic therapy 33 . In the short term, the use of second and third line antibiotics can improve the cure rate, reduce the direct and indirect costs for individual and society, but in the long term, the use of antibiotics across the ladder will lead to the increase and spread of resistance of advanced antibiotics, so for the rational application of antibiotics, clinicals need to balance individual and societal needs.…”
Section: Discussionmentioning
confidence: 99%